As the world ages : rethinking a demographic crisis - Sivaramakrishnan, Kavita (Harvard University Press, 2018)
People are living longer, not only in wealthy countries but in developing nations. Western experts have long conceived of aging as a universal predicament--one that supposedly provokes the same welfare concerns in every context. In the twenty-first century, we must embrace a new approach that prioritizes local agendas and values. In this history of how gerontologists, doctors, social scientists, and activists came to define the issue of global aging, Sivaramakrishnan shows that the United Nations, private NGOs, and transnational philanthropic foundations embraced programs that reflected prevailing Western ideas about modernization. The dominant paradigm often assumed that, because large-scale growth of an aging population happened first in the West, developing societies will experience the issues of aging in the same ways and on the same terms as their Western counterparts. Focusing on South Asia and Africa, As the World Ages shows how regional voices have begun to question this one-size-fits-all model and have argued instead for an approach that responds to local needs and concerns.--